Description of Macro Nutrition Intake, Snack Consumption Habits with Nutritional Status in Elementary School Children at UPT SDN 86 Gresik - Putri Mahardika; Nuning Marina Pengge; Taufiqurrahman; Riezky Faisal Nugroho; Fahmi Hafid; Sarina Sariman (Politeknik Kesehatan Kemenkes Surabaya, 2024)
The nutritional status of school children can be influenced by food consumption and snacking habits, potentially leading to malnutrition and obesity. This study aims to identify the profile of macro-nutrient intake, snacking habits, and the nutritional status of elementary school children at UPT SDN 86 Gresik. It is descriptive in nature and involves 82 students as respondents. The survey method was utilized, employing questionnaires and interviews for data collection. The research conducted at UPT SDN 86 Gresik revealed that 46.7% of students had an energy deficit, 62.2% had a protein deficit, 64.4% had a fat deficit, and 57.8% had a carbohydrate deficit. Additionally, 42.2% exhibited poor snacking frequency, and 60% consumed unhealthy snacks. Based on the research findings, it can be concluded that 4 students (8.9%) had poor nutritional status, 32 students (68.9%) had a normal nutritional status, 2 students (4.4%) had excess nutritional status, and 7 students (15.6%) were obese